INTERAKSI KOMITMEN ORGANISASI TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Dina Fitri Septarini; Frans Papilaya (Universitas Musamus,Merauke,Papua, 2016)
Audit BPK for the financial statements 2013 of Merauke district received a qualified opinion. This means that there are other things that should be repaired in the preparation of financial statements. Therefore, this study aimed to determine the effect of the competence of the Human Resources and internal control system to the quality of financial reports of local government, and the moderating influence of organizational commitment on the relationship between HR competencies and internal control system to the quality of financial statements of local government Merauke. This study uses a quantitative approach and the collection of primary data in this study using a survey by questionnaire to respondents selected as the sample. The population in this study is the employees of the finance department at regional work units (SKPD) of Local Government Merauke, totaling 29 SKPD. The sampling technique used is purposive sampling, ie sampling specific criteria. The data analysis technique used to test the effect of independent variables on the dependent variable regression analysis of interaction or Moderated Regression Analysis (MRA) with SPSS 20. The results showed that the Human Resource Competency positive effect on the quality of local government financial statements, Systems the internal control does not affect the quality of local government financial statements, organizational commitment moderates the relationship between human resources competencies to the quality of local government financial statements, and organizational commitment does not moderate the relationship between the internal control system to the quality of local government financial reports.